Which expression is equivalent to 3(5 + 6)?8 + 9
8 + 6
15 + 18
15 + 6

Answers

Answer 1
Answer: The third one is correct, because if you distribute, you will get 15 + 18
Answer 2
Answer: First solve
3(5 + 6).
5+6=11
Now 3*11=33
So now which of the answers also=33?
8+9=17 so no
8+6=14 so no aswell
15+18=33 therefore this is correct. so your answer is c.
15+6=21 so no


Related Questions

What is the slope of AC?
if a humming bird were to get all of its food from a feeder then a 16 oz nectar feeder could feed about 80 humming birds a day how many humming birds would you expect to be able to feed with a 12 oz feeder?
How many decameters are there in 14 meters
Iodine-125 has a half-life of about 60 days.How many milligrams of a 500 mg sample will remain after 300 days? 1. 0.6 mg 2. 7.8125 mg 3. 15.625 mg 4. 31.25 mg
The ideal length of a particular metal rod is 30.5 cm. The measured length may vary from the ideal length by at most 0.015 cm. What is the range of acceptable lengths for the rod?

A graph Includes the ordered pair (2,4). Write two different rulesA graph Includes the ordered pair (2,4). Write two different rules that would be possible for this graph. Explain how you found your answer.

Answers

All you have to do is make up some answers that when the ordered pair is substituted, it is a valid answer. 

Here are some I made up: 

y=2x 

and 

y=x+2 

When substituting your ordered pair into this, it will be correct. 

Hope this helped! 

~Cam943, Moderator

Cheddar cheese costs £7.50 for 1kg.Marie buys 200 grams of cheddar cheese.How much does she pay?(PLEASE SHOW WORKING OUT)

Answers

There are 1000g in a kilogram.
1000÷200=5
£7.50÷5=£1.50
The answer is £1.50

Hope this helped.

How to justify a/b x b/c = a/c?

Answers

a/b times b/c is = ab/bc
which can be written as a/c times b/b
anything over itself is 1 so b/b is one
a/b times b/c = a/c
well a/b * b/c = ab/bc, and since b/b= 1 you get 1a/c or just a/c :)

Exponents 5.5.5.b.b.b.b

Answers


125 {b}^(3)

Solve the equation. Select all that apply.x^2= 121
A
x = 11
B. x=21
C. X = 61
D. x=-11
E. X=-21

Answers

Answer:

x = 11, x = -11

Step-by-step explanation:

I know this is kind of late but the two previous answers were wrong.

We have x² = 121. To find x, we need to get rid of the exponent, and to do this, we can take the square root of both sides:

√x² = √121

x = √121

You might think that x = 11 but remember, x can be negative as well because you can square negative numbers. Basically, every real number has two square roots - a positive and a negative one. So, the answer isn't just x = 11, it's also x = -11 because (-11)² = 121 as well.

Answer:

x=11

Step-by-step explanation:

Rewrite the expression without using grouping symbols. -6(8+12)

Answers

-6(8+12)=-48-72
-6(8+12)=-6\cdot8+-6\cdot12=-48+(-72)=-48-72

I hope I helped :D